Physiology and Medicine at High Altitude: The Exposure and the Stress - Gurtoo, Anil (Defence Life Science Journal, 2018)
Increase in altitude causes decrease in atmospheric barometric pressure that results in decrease of inspired partial pressure of oxygen, a source for stress and pose a challenge to climbers/trekkers or persons posted on high altitude areas. This review discusses about the high altitude sickness, their incidence rates, pathophysiology and the classic model of acclimatisation, which explains about how oxygen requirement in extreme environment is achieved by complex interplay among pulmonary, hematological and cardiovascular processes. The acute high altitude illness (AHAI) is basically composed of two syndromes: cerebral and pulmonary that can afflict un-acclimatised climbers/trekkers. The cerebral syndrome includes acute mountain sickness (AMS) and high altitude cerebral oedema (HACO) and pulmonary syndrome typically refers to high altitude pulmonary oedema (HAPO). The core physiological purpose, according to the classic model is centered upon the optimisation of increased delivery of oxygen to the cells through a coherent response involving increased ventilation, cardiac output and hemoglobin concentration with aim to increase the oxygen flux across the oxygen cascade, which will help in preventing the development of majority of high altitude illness.